Exploring the desire of Filipino engineering professionals to work abroad using the ECT-TPB Theory - Rex Revian A. Guste; Ardvin Kester S. Ong; John Francis T. Diaz; Maela Madel L. Cahigas; Ma. Janice J. Gumasing (Acta Psychologica)
The rising globalization of the workforce needs an awareness of the elements that influence professionals' decisions to work overseas. Especially in the Philippines where professionals are migrating abroad, there is little to no literature available for the behavioral intention and satisfaction of the movement. This study considered an integrated theoretical model based on the Extended Theory of Planned Behavior (TPB) and Expectation-Confirmation Theory (ECT) to analyze the factors influencing Filipino engineering professionals' aspirations to work overseas. Data were obtained from 256 engineers who worked abroad and analyzed using structural equation modeling. Results showed how confirmation has a substantial impact on satisfaction, which in turn influences the willingness to pursue overseas assignments. Expectation influences confirmation as the second most important component, although its direct effect on satisfaction is insignificant. The study revealed that confirmation indirectly affected behavioral intentions more than expectation, implicating to be the driver of satisfaction among Filipino engineering professionals interested in working overseas. Moreover, confirmation is strongly influenced by expectation, and pleasure has a considerable impact on behavioral intention. Attitude and perceived behavioral control are also important factors in forming the intention to work abroad, although subjective norms have less influence. The findings offer managerial insights locally on how to improve the workforce and culture of engineering professionals in the Philippines, hence could increase job satisfaction and commitment to local employment. Lastly, the integrated model provides a comprehensive picture of the elements influencing expatriation intentions and serves as a solid foundation for future study on professional mobility.